Hierarchical detection of wildfire flame video from pixel level to semantic level. Issue 8 (15th May 2015) - Zhao, Yaqin; Tang, Guizhong; Xu, Mingming
Highlights Propose a flame region detection method using sparse representation of flame block. Establish a flame recognition model of based on mathematical model of meaning. Identify flame video from low-level visual features to high-level semantics. Validate higher accuracy of the proposed method with comparable computational time.